Concomitant ventricular septal rupture and interventricular septal aneurysm in neglected inferior myocardial infarction misdiagnosed with congenital ventricular septal defect: A case report. Issue 10 (18th October 2021) - Davarpasand, Tahereh; Mohseni‐Badalabadi, Reza; Sadeghian, Mohammad; Mortazavi, Seyedeh Hamideh; Lalvand, Atefeh
Abstract: This study emphasizes that VSD should not be immediately diagnosed as a congenital disorder; instead, regional wall motion abnormalities in the left ventricle should also be taken into account since it may result from mechanical complications of neglected myocardial infarction. Abstract : This study emphasizes that VSD should not be immediately diagnosed as a congenital disorder; instead, regional wall motion abnormalities in the left ventricle should also be taken into account since it may result from mechanical complications of neglected myocardial infarction.